2020
DOI: 10.1515/ling-2020-0092
|View full text |Cite
|
Sign up to set email alerts
|

Partitivity in Slavic-Romance language contact: The case of Molise Slavic in Italy

Abstract: Molise Slavic is a south Slavic micro-language, spoken in three municipalities in the Italian region of Molise. It has been in a situation of total language contact with Romance varieties for about 500 years, with strong foreign influence on all linguistic levels. This paper is intended as a contribution to two combined fields of linguistics: contact linguistics and the expression of partitivity in Slavic in different settings. The paper opens with a short description of the position of the (morphological) par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In contrast to the rather "unidirectional" areal cline, it is less clear where the loss of irrealis restrictions of da began; the most probable "candidates" are the northwestern end (early Slovene, Kajkavian) and the Adriatic coast (čakavian); cf. Grković-Major (2004;2020) and Greenberg (this volume). In either case, language contact (with German, Vulgar Latin or Italian, respectively) can be assumed to have been a catalyst of this process.…”
Section: Patterns Of Clausal Complementationmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast to the rather "unidirectional" areal cline, it is less clear where the loss of irrealis restrictions of da began; the most probable "candidates" are the northwestern end (early Slovene, Kajkavian) and the Adriatic coast (čakavian); cf. Grković-Major (2004;2020) and Greenberg (this volume). In either case, language contact (with German, Vulgar Latin or Italian, respectively) can be assumed to have been a catalyst of this process.…”
Section: Patterns Of Clausal Complementationmentioning
confidence: 98%
“…It is in such situations that the concept of a common diasystem or diagrammar of the two (or more) languages in question becomes evident. The concept of "diagrammar" is a theoretical model based on the hypothesis that multilingual speakers do not strictly separate the grammars of their two or more languages but combine them in the most economical way possible; see Breu (2011: 440) and Breu (2019bBreu ( , 2020. It could be argued that the grammars of the individual languages in contact are synchronically derived from their diagrammar, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of Italian seems obvious here as Italian has lost neuter gender. But neuter gender does remain in MOL.Cro as a relic form in specific contexts, namely with adjectives and pronouns in impersonal utterances (see below section 6.1.1) Breu (2013a). has shown that the contact situation accounts even for retention of neuter gender in MOL.Cro adjectives, due to the model of Molise Italian that itself has retained neuter gender in this case.…”
mentioning
confidence: 93%